2022
DOI: 10.61136/khid.v2i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Al-Qur’an Educational Park Management to Increase the Quality of Non-Formal Education

Abstract: The management of the Al-Qur’an Education Park in TPQ Jombong hamlet Paten Dukun is a way of managing a non-formal educational institution starting from planning, organizing, implementing, monitoring, and evaluating in order to achieve the goals of TPQ in Hamlet Jombong. The background in this study is that TPQ in Jombong Hamlet aims to educate children who are Qur’anic generations. Therefore, the TPQ in Jombong Hamlet requires management within the institution. This research aims to manage TPQ in Jombong Haml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Based on some of the explanations above, it can be concluded that the Qur'an is a holy book sent down by Allah SWT as a miracle which in essence must be read and interpreted in every word and must be practiced for Muslims (Rohmah et al, 2016;Usiono et al, 2021;Mutathahirin et al, 2022). Reading, interpreting and practicing it is an obligation for Muslims, but the initial phase that is carried out before interpreting and practicing the Qur'an is of course knowing how to read it (Farida et al, 2021;Salmia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on some of the explanations above, it can be concluded that the Qur'an is a holy book sent down by Allah SWT as a miracle which in essence must be read and interpreted in every word and must be practiced for Muslims (Rohmah et al, 2016;Usiono et al, 2021;Mutathahirin et al, 2022). Reading, interpreting and practicing it is an obligation for Muslims, but the initial phase that is carried out before interpreting and practicing the Qur'an is of course knowing how to read it (Farida et al, 2021;Salmia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of the ability to read the Qur'an among Muslims is actually a universal issue. Various studies have proven that the ability of Muslims to read the Qur'an is still weak, and not a few are still blind to reading the Qur'an (Damanik, 2019;Rohmah et al, 2016;Wahyuni, 2021). Therefore, this problem must be of concern to various parties, such as the government, the community, more specifically universities that have Islamic religious education departments, as it is known that students studying in this department will be educated as religion teachers in schools, of course they must be equipped with competence.…”
Section: Introductionmentioning
confidence: 99%